Non-financial reporting of chemical companies in the Czech Republic - Munzarova, Simona; Kostalova, Jana; Fialova, Eliska (Business: Theory and Practice, 2022)
This paper focuses on the issue of non-financial corporate reporting by the Czech chemical companies. Based on the content analysis of the websites and disclosures, it analyses, compares and evaluates the level of web communication of the economic, environmental and social issues of corporate social responsibility of these companies. At first, it presents results of the research comparing the extent of non-financial web communication of selected Czech chemical companies with the Czech leaders in the Czech TOP 100 rankings. These results are then complemented by results of the quantitative research on environmental instruments used by all Czech chemical production companies, that use websites for communication of their activities. The number of companies in the Czech Republic processing non-financial reports is significantly lower than abroad, but it is still growing. Large enterprises pay more attention to non-financial reporting. Rather than including this information in a disclosure, a business website is used as a tool for this communication. The paper brings sectoral perspective into non-financial reporting literature, as attention is paid to the chemical production sector and also complements the knowledge of communication of companies that do not belong to the group of 100 most important companies within the country.